Paraneoplastic glomerular disease. Case study - Leonid I. Dvoretsky; Nina A. Sidoruk; Sergei A. Krivushkin; Ekaterina S. Stolyarevich; Svetlana E. Kolendo; Andrei P. Stepanchenko (LLC "MEDIAFORMAT", 2022)
The case of membranous nephropathy manifested in nephrotic syndrome in a patient, newly diagnosed with lung cancer, is reported. Brief data on the paraneoplastic glomerular disease are provided, the need for cancer screening in elderly patients with nephrotic syndrome is emphasized.